2013
DOI: 10.1523/jneurosci.4760-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Fast Modulation of Executive Function by Language Context in Bilinguals

Abstract: Mastering two languages has been associated with enhancement in human executive control, but previous studies of this phenomenon have exclusively relied on comparisons between bilingual and monolingual individuals. In the present study, we tested a single group of WelshEnglish bilinguals engaged in a nonverbal conflict resolution task and manipulated language context by intermittently presenting words in Welsh, English, or both languages. Surprisingly, participants showed enhanced executive capacity to resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
155
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(195 citation statements)
references
References 42 publications
25
155
7
Order By: Relevance
“…Few of the recent reports on consequences of bilingualism have identified specific aspects of language use that may be associated with the consequences that have been claimed for cognitive control mechanisms and for the neural circuitry that supports them. The few that have been suggested are focused primarily on lexical processes (e.g., Blumenfeld & Marian, 2011; Wu & Thierry, 2013). The significance of the present results is thus in identifying a specific instance of the tuning of the language comprehension system to a set of naturally occurring features in the output from the language production system, and in suggesting that such tuning may be a critical aspect of enabling fluent performance.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the recent reports on consequences of bilingualism have identified specific aspects of language use that may be associated with the consequences that have been claimed for cognitive control mechanisms and for the neural circuitry that supports them. The few that have been suggested are focused primarily on lexical processes (e.g., Blumenfeld & Marian, 2011; Wu & Thierry, 2013). The significance of the present results is thus in identifying a specific instance of the tuning of the language comprehension system to a set of naturally occurring features in the output from the language production system, and in suggesting that such tuning may be a critical aspect of enabling fluent performance.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive control requires a narrowing of attention that is arguably enhanced when participants must use one rather than another language in a dual language context. An ingenious experiment by Wu and Thierry (2013) found that during a dual language context, bilinguals were indeed more effective at resisting non-verbal interference as tested in a non-verbal flanker task (see also (Hommel et al 2011) for evidence of benefits on a convergent thinking task). Cooperative control, by contrast, is predicted to increase the breadth of attention.…”
Section: Language Control Statesmentioning
confidence: 99%
“…Furthermore, the majority of research in this field involves comparisons between monolinguals and bilinguals and studies examining within-bilingual comparisons are scarce (but see Wu & Thierry, 2013). As such, some researchers remain critical of these group comparisons given that extraneous variables may have confounded results (e.g., socioeconomic status, culture) (Morton & Harper, 2007).…”
Section: Introductionmentioning
confidence: 99%